Taxonomy, geographic distribution, conservation and species boundaries in Calydorea azurea group (Iridaceae: Tigridieae) - Deble, Leonardo Paz; Oliveira Deble, Anabela Silveira de; Alves, Fabiano da Silva; Garcia, Luiz Felipe (Balduinia, 2018)
For this study were performed observations in populations of Calydorea azurea Klatt and allied taxa, along of the ecosystems of the Río de La Plata Grasslands, geographic extent where occur this group. For the complementation of the data were examined collections deposited in the principal herbaria of southern Brazil, Uruguay and Argentina, and were analyzed image of types and others collections available. All studied species were photographed and its populations geo-referenced. It are recognized six species: C. alba Roitman & Castillo, C. azurea, C. charruana Deble, C. luteola (Klatt) Baker, C. minima Roitman & Castillo and C. riograndensis Deble. C. azurea is cited for Brazil, C. charruana is added to Argentinian flora, C. luteola has its taxonomic delimitation established, and its occurrence is extended up to the northern Uruguay. The geographic distribution of C. riograndensis is reestablished, in view of three collections mentioned in the protologue are identified as belonging at others species. All species studied are described, illustrated through of photos, being presented data about geographic distribution, ecology and conservation.